Implementasi Kebijakan Pengarusutamaan Gender dalam Pelaksanaan Tugas dan Fungsi Dewan Perwakilan rakyat Republik Indonesia - Ida Fauziyah (Institut Pemerintahan Dalam Negeri (IPDN), 2020)
The implementation of gender mainstreaming policies in the implementation of the duties and functions of the DPR has not been optimal to support the realization of gender equality and justice in the life of society, nation and state, especially to improve the position, role and quality of women. However, it must be admitted that the implementation of the DPR's duties and functions is one of the determining factors for the successful implementation of gender mainstreaming policies in national development. This, among others, was revealed by a number of legislation products that were more responsive to gender issues and increased women's representation in parliament. With the Grindle public policy implementation model, it is possible to reveal the performance of the gender mainstreaming policy according to the parameters of the interests affected; type of benefits; extent of change envisioned; site of dicision making; program implementor; resource committed; power, interests, and strategies of actors involved; institution and characteristic regime; compliance and responsiveness. The new concept is composed of the Strategy for Implementing Gender Mainstreaming Policies in National Development with the definition: Strategy for Implementing Gender Mainstreaming Policies in National Development, which are structured strategies, tips and methods in implementing policies, programs and activities to improve the position, role and quality of women to achieve equality and gender justice which consists of a formal legality strategy, a structural synergy strategy, a cultural adaptation strategy, and an individual strengthening strategy.